창업 의도에 대한 기업의 사회적 책임 인식과 기업가적 역량·태도의 영향: 창업 교육의 조절효과 분석 - 장문경; Moonkyoung Jang (벤처창업연구, 2025)
In recent years, both domestically and internationally there has been a growing critical perspective on corporations, accompanied by increasing interest in the ethics and social responsibility of corporate activities. As a result, perceived corporate social responsibility has emerged as a crucial factor influencing entrepreneurial intention. Against this backdrop, this study investigates the impact of negative perceived corporate social responsibility on entrepreneurial intention and examines the moderating role of entrepreneurship education in this relationship. Specifically, key determinants of entrepreneurial intention, such as entrepreneurial competence, entrepreneurial attitude, and perceived corporate social responsibility, were analyzed alongside the moderating effects of entrepreneurship education. To empirically test these relationships, this study utilized data from the "Entrepreneurship Survey (Individual Section)" conducted by the Korea Entrepreneurship Foundation (KoEF). Hierarchical regression analysis, performed using Stata 14, was employed to verify the direct and moderating effects among the variables. The results revealed that negative perceived corporate social responsibility significantly reduces entrepreneurial intention, while entrepreneurial competence and entrepreneurial attitude positively influence it. Although entrepreneurship education did not directly enhance entrepreneurial intention, it played a significant moderating role in alleviating the negative impact of perceived corporate social responsibility. However, its moderating effect on entrepreneurial competence was not statistically significant, and its influence on entrepreneurial attitude differed from expectations. This study makes both academic and practical significance by empirically demonstrating how social and psychological perceptions of corporations shape entrepreneurial intention, based on a large-scale, representative sample of the general Korean population. Moving beyond the traditional emphasis on competence and attitude, the findings highlight the critical role of entrepreneurship education in mitigating negative perceived corporate social responsibility. This insights highlight the necessity of developing policies and educational programs that cultivate a balanced perception of corporate activities and foster a more supportive entrepreneurial environment. 최근 기업 활동의 윤리성과 사회적 책임에 관한 관심이 높아지면서, 창업 의도 형성에도 기업의 사회적 책임에 대한 인식이 중요한 변수로 드러나고 있다. 이에 본 연구는 기업이 사회적 책임을 다하지 않는다는 부정적 인식이 개인의 창업 의도에 미치는 영향을 탐색하고, 이 관계에서 창업 교육 경험이 어떤 조절 역할을 하는지 규명하고자 하였다. 이를 위해 기업의 사회적 책임에 대한 인식이 창업 의도에 미치는 영향을 분석할 때, 기존 연구에서 주요하게 다뤄진 기업가적 역량과 기업가적 태도를 함께 고려하였으며, 더불어 창업 교육 경험의 조절 효과를 분석하였다. 연구 데이터로 한국청년기업가정신재단(KoEF)이 실시한 '기업가정신 실태조사(개인편)' 데이터베이스를 활용하였으며, 계층적 회귀분석을 적용하여 각 변인 간의 관계와 조절 효과를 검증하였다. 분석 결과, 기업이 사회적 책임을 다하지 않는다는 부정적 인식은 창업 의도에 유의미한 부정적 영향을 미쳤으며, 기업가적 역량과 기업가적 태도는 모두 창업 의도를 높이는 데 긍정적 요인으로 작용하는 것으로 나타났다. 한편, 창업 교육 경험이 창업 의도에 직접적인 영향을 주지는 않았지만, 기업이 사회적 책임을 다하지 않는다는 부정적 인식이 창업 의도에 미치는 부정적 효과를 완화하는 유의미한 조절 효과를 보였다. 반면, 기업가적 역량에 대한 창업 교육 경험의 조절효과가 통계적으로 유의하지 않았으며, 기업가적 태도에 대해서는 교육 경험의 조절 효과가 예상과 다르게 부정적으로 유의미하게 나타났다. 본 연구는 KoEF 기업가정신 실태조사(개인편)를 활용하여 국내 일반 국민을 폭넓게 포함한 대규모 표본을 기반으로 기업의 사회적 책임에 대한 인식이 창업 의도에 미치는 영향을 실증적으로 확인했다는 점에서 의의를 지닌다. 특히, 기존 연구가 개인 차원의 역량이나 태도에 집중했던 것에서 나아가, 기업이 사회적 책임을 다하지 않는다는 부정적 인식을 완화하는 데 있어 창업 교육의 중요한 역할을 강조함으로써, 향후 창업 관련 정책 및 교육 프로그램 설계 시 기업 및 기업가에 대한 긍정적 이미지를 제고하는 방안을 더욱 구체적으로 모색할 필요성을 제기한다.